ACTIVITY OF INDIAN TOPICAL SKIN PHARMACEUTICALS AGAINST SOME FUNGAL PATHOGENS - Javed Iqbal, (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The aim was to assess the in vitro antifungal activity of some locally available pharmaceutical preparations used to cure skin diseases. Most commonly used preparations were evaluated for dermatophytic and non-dermatophytic fungi viz., Aspergillus niger, Trichophyton rubrum, Candida albicans, rhizopus microspores and Cryptococcus neoformis. Methods: Disc diffusion method was used for inhibition zone of different preparations. Results: When compared with different preparations used against skin diseases, Zalim lotion were found to be highly active against T. rubrum, C. albicans, Rhizosporus microsporus. Conclusion: The result obtained from the experiment suggests broad spectrum activity of Zalim lotion against dermatophytic and non-dermatophytic fungi. Keywords: Antifungal, Tinea, Dermatophytic, Rubrum, Aspergillus.